2023
DOI: 10.1149/1945-7111/accc57
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal of Ammonia and Nitrate from Wastewater Using a Pulse Electrolysis Technique

Abstract: The Environmental Protection Agency considers ammonia and nitrate as large-scale threats to environmental quality and human health, causing impaired air quality, surface water eutrophication, and other serious health problems. This work examines the viability of using a pulse electrolysis technique to accomplish the simultaneous removal of ammonia and nitrate in an undivided flow cell using CuNi/PtIr supported on carbon electrocatalysts (CuNi/PtIr/C). Different series of PtIr/C and CuNi/C compositions were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…This showed increased hydrogen ions in the wastewater affecting the pH, decomposition activity, and increasing NH3 gas retention. Dey et al [40] and Hariri and Botte [41] observed that untreated organic matter in WRRFs decomposes over time; this results in pH imbalances, as well as the proliferation of NH3. Temperature had a negative significant loading…”
Section: Principal Component Analysis Results For Physicochemical Var...mentioning
confidence: 99%
See 2 more Smart Citations
“…This showed increased hydrogen ions in the wastewater affecting the pH, decomposition activity, and increasing NH3 gas retention. Dey et al [40] and Hariri and Botte [41] observed that untreated organic matter in WRRFs decomposes over time; this results in pH imbalances, as well as the proliferation of NH3. Temperature had a negative significant loading…”
Section: Principal Component Analysis Results For Physicochemical Var...mentioning
confidence: 99%
“…This showed increased hydrogen ions in the wastewater affecting the pH, decomposition activity, and increasing NH 3 gas retention. Dey et al [40] and Hariri and Botte [41] observed that untreated organic matter in WRRFs decomposes over time; this results in pH imbalances, as well as the proliferation of NH 3 . Temperature had a negative significant loading (component loading <−0.5); this indicated low temperature levels which lead to minimal microbial reactions and the extirpation of gases such as NH 3 , CO 2 , and CH 4 .…”
Section: Principal Component Analysis Results For Physicochemical Var...mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently Hariri and Botte demonstrated electrocatalysts combination (PtIr, CuNi) and a cell configuration that enables the simultaneous removal of both ammonia and nitrate from wastewater with hydrogen cogeneration. 26 Implementing the NH 3 electrolysis method kills two birds in one stone more efficient H 2 production and addresses wastewater problems (minimizing environmental impact air, water, and land). The source of ammonia comes from various industrial and agricultural waste streams, which not only provides feedstock for hydrogen production but also mitigates environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic ammonia oxidation reaction (EAOR) has potential applications in the fields of energy conversion and wastewater treatment. 1–4 In particular, considerable attention has been paid to the applications of ammonia fuel cells and on-line hydrogen production in recent years due to the remarkable advantages of ammonia as an energy carrier regarding its high hydrogen content, carbon-free nature, easy storage and transportation. 5–7 In the EAOR, ammonia is expected to be oxidized to N 2 at the anode, and water is reduced to H 2 at the cathode:Anode: 2NH 3 (aq) + 6OH − → N 2 + 6H 2 O + 6e − E ° = −0.77 V vs. SHECathode: 6H 2 O + 6e − → 3H 2 + 6OH − E ° = −0.83 V vs. SHEOverall reaction: 2NH 3 (aq) → N 2 + 3H 2 E ° = −0.06 V…”
mentioning
confidence: 99%